Distribution patterns of gas content in Vorobyov deposits within the southern dip of the Buzuluk depression - D. D. Mikhalchenko; P. N. Strakhov; G. N. Potemkin; I. D. Loginov (Известия высших учебных заведений: Геология и разведка)
Background. The southern immersion of the Buzuluk depression remains one of the most promising areas of oil and gas production in the Orenburg region due to significant residual reserves and favorable characteristics of Devonian deposits. The deposits of this region are characterized by a complex geological structure, high gas factor (more than 1000 m3/t) and stable oil reserves, which requires the use of modern geological and technical solutions. Despite the relatively high level of knowledge, due to the complex structure and features of fluid dynamics, the development of mature deposits is accompanied by a number of challenges and remains relevant for further research.Aim. Identification of spatial patterns of the distribution of the gas content of reservoir oils within the southern immersion of the Buzuluk depression.Materials and methods. The results of geological and commercial research and development data were used as source materials. Methods of structural and geological analysis, comparison of the gas content and the tectonic position of deposits are applied.Results. The values of the gas content of the Vorobyovsky horizon oil deposits (formation DIV) within the southern and central parts of the Buzuluk depression demonstrate significant variability. An analysis of the spatial distribution of the parameter showed the presence of a general trend of increasing gas content from the Bobrovsko-Pokrovsky shaft towards the Kamelik-Chagan structural zone. At the same time, the highest values (up to 902 m3/t) were recorded in individual deposits of the structural zone. However, the structural and tectonic analysis did not reveal a direct and stable relationship between the amount of gas content and tectonic confinement. The established patterns are rather local in nature and may be due to the combined influence of lithological, stratigraphic, tectonic, thermobaric and fluid dynamic factors.Conclusion. A general trend has been established towards an increase in the gas content of reservoir oils towards the southern boundary of the Buzuluk depression. The data obtained indicate the multicomponent nature of the formation of abnormally high values of gas content.